Assesment of Activities of a Chamber of Commerce - Sedláková, Julie (2025)
The aim of this thesis is to explore and critically assess the wide portfolio of the activities of the British Chamber of Commerce in the Czech Republic (BCC). The thesis explores its strengths, weaknesses, as well as possible threats and opportunities, which can be used to formulate suggestions for improvement to make the BCC activities more efficient. The research to explore this topic combines qualitative and quantitative methods, most notably an in-depth interview with a former senior BCC manager, supported by a quantitative data analysis, both revealing essential information regarding the Chamber's structure, membership and member engagement, and event strategy. The findings reveal several key strengths of the BCC, including its highly active event calendar, strategic member acquisition, and flagship mentoring programme, which significantly all contribute to the Chamber's reputation and value. The analysis also identifies weaknesses such as the absence of a systematic process for gathering member motivations and feedback, and occasional misalignment between organized events and actual member interest. Opportunities lie in expanding engagement among smaller members and exploring partnerships with external experts to enrich content. Meanwhile, threats such as competition from other chambers and maintaining relevance across diverse member needs are identified. The analysis concludes that while the BCC is successful in fulfilling its mission of fostering meaningful business connections and promoting trade between the United Kingdom and the Czech Republic, targeted improvements in the areas of event planning, strategic positioning, and expanded collaboration could further enhance its impact to maximize its effectiveness and impact.